Silenced victims of wartime sexual violence - Simic, Olivera (Post-conflict law and justice, 2018)
The book focuses on the experiences of Bosnian Serb women, where the collapse of the former Yugoslavia led to brutal war and gross human rights violations throughout the 1990s. Two decades after the war, women in Bosnia and Herzegovina are still facing the legacies of the violence in the 1990s.